The Role of Respiratory Control in Radiation Therapy Management - Ronald, Andreas; Gondhowiardjo, Soehartati Argadikoesoema (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2023)
The goal of radiotherapy is to eradicate the tumor but still consider the surrounding normal organs. However, this is not easy to achieve because there are many factors that influence the process of external radiation. These factors are broadly divided into 2, namely intra-fraction motion and inter-fraction motion. It contributes to acute and late effect. These acute and late effects can be an obstacle in attempting to increase the dose in the tumor. this literature review will discuss the problems and developments of radiation techniques in relation to intra-fraction problems due to respiratory movements.